1989
DOI: 10.1364/ao.28.003166
|View full text |Cite
|
Sign up to set email alerts
|

Statistical-mode sensor for fiber optic vibration sensing uses

Abstract: A method of sensing vibration using the detection of changes in the spatial distribution of energy in the output of a multimode optical fiber has been demonstrated. Two implementations of the sensor have been built and tested. The first implementation involved simple optical processing of the output fiber speckle pattern using spatial filtering. The second implementation involved projecting the pattern on a CCD array and digitally processing observed changes in the intensity distribution. A mathematical model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(70 citation statements)
references
References 4 publications
0
61
0
5
Order By: Relevance
“…This transmission is governed by Fresnel reflection coefficients. In equation (2), it can be clearly seen that the bent fiber is influenced by the refractive index of the external environment, so it implies that the system is sensitive to liquid media and their concentrations.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…This transmission is governed by Fresnel reflection coefficients. In equation (2), it can be clearly seen that the bent fiber is influenced by the refractive index of the external environment, so it implies that the system is sensitive to liquid media and their concentrations.…”
Section: Theorymentioning
confidence: 99%
“…Since the speckle pattern in the output fiber varies slowly with time, this pattern is sensitive to disturbances such as temperature, pressure or vibration in the fiber, which can be obtained by a suitable speckle pattern processing [1]. By taking advantage of this characteristic, various schemes and assemblies of sensors based on the speckle generated in multimode optical fibers have been proposed [2][3][4][5].Those configurations have advantages over conventional systems due to their low cost, insensitive to electromagnetic interference, flexible, lightweight and easy installation. Spillman et al demonstrated a method using vibration sensing changes in the spatial distribution of energy in the exit end of a multimode fiber [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, fiber specklegrams can be used for sensing purposes. Since the 1980s, numerous designs and arrangements of sensors based on fiber specklegram have been proposed to measure vibration, displacement, strain, and acoustic waves [3][4][5][6]. These first sensors using bulky assemblies and signal processing was very extensive and laborious.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the use of a bare polymer optical fiber is proposed as an acoustic sensor for normalization purposes, based on the sensing principle of speckle interferometry [16]. This effect is extremely sensitive to mechanical perturbations of the optical fiber and has the potential to surpass the performance of conventional microphones.…”
Section: Introductionmentioning
confidence: 99%